2022
DOI: 10.2166/ws.2022.129
|View full text |Cite
|
Sign up to set email alerts
|

Discharge coefficients for ogee spillways

Abstract: Discharge over an ogee weir is related to the length of weir, upstream total head above the weir crest and the discharge coefficient. The discharge coefficient is influenced by several factors; in this study, some parameters that influence discharge coefficients of ogee weirs are investigated. These factors include: the weir upstream slope, apron elevation, and downstream submergence. In this regard, ogee weir physical models were fabricated. These models comprise: an ogee weir with a vertical upstream face, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In 2022, Salmasi and Abraham [38] analyzed the influence of the upstream slope of the spillway and the downstream submergence. Their results showed that, for all standard ogee spillways, the discharge coefficient (C) increases with increasing P/H, and then reaches a constant value.…”
Section: 𝑄 = 𝐶𝐿𝐻 /mentioning
confidence: 99%
“…In 2022, Salmasi and Abraham [38] analyzed the influence of the upstream slope of the spillway and the downstream submergence. Their results showed that, for all standard ogee spillways, the discharge coefficient (C) increases with increasing P/H, and then reaches a constant value.…”
Section: 𝑄 = 𝐶𝐿𝐻 /mentioning
confidence: 99%
“…More recently, in 2022, Salmasi and Abraham [34] analyzed the influence of the upstream slope of the spillway and the downstream submergence. Their results showed that for all standard ogee spillways, the discharge coefficient (𝐶) increases with increasing 𝑃𝐻 ⁄ , and then reaching a constant value.…”
Section: 𝑄=𝐶 𝐿𝐻 /mentioning
confidence: 99%
“…Usually, on channels, the Reynolds number is large enough so the effect of viscosity can be neglected. Salmasi and Abraham's (2022) studies showed that the effect of the surface tension could also be ignored if the water head on the weir is higher than 3 to 4 cm. Thus, the Weber and the Reynolds numbers are removed from Equation (3).…”
Section: Dimensional Analysesmentioning
confidence: 99%